Applying refinery outgoing gas as a source of petrochemical products - A. I. Absattarov; Yu. A. Pisarenko; N. I. Zelentsova (Тонкие химические технологии)
The problem of applying refinery outgoing gas (ROG) is considered in this article. Today this gas containing ethylene and propylene doesn’t have any usage in Russia. But it could be a good feedstock for petrochemical industry. In view of ethylene deficiency, the recovery of ethylene from refinery outgoing gas is a very important problem. In order to solve this problem the advantage of applying ROG as an alternative feedstock for ethylene production was suggested in this article. Various methods of applying refinery outgoing gas were introduced. The economic advisability was demonstrated. The technology of gas purification was suggested. Combination of refinery processes and ethylene production allows increasing the degree of petroleum refining and getting profit by recovering ethylene from ROG.